Sodium-Glucose Cotransporter-2 (SGLT2) Inhibitors: A Clinician’s Guide - Simes BC (Dove Medical Press, 2019)
Bryce C Simes, Gordon G MacGregor Alabama College of Osteopathic Medicine, Dothan, AL, USACorrespondence: Bryce C SimesAlabama College of Osteopathic Medicine, 445 Health Sciences Blvd., Dothan, AL 36303, USATel +1 205 904-504-8897Fax +1 205 334-699-2268Email simesbc@acom.eduAbstract: This comprehensive review covers the historical background, physiology, application in type 2 diabetes, novel uses, cardiovascular benefits, side effects and contraindications of sodium-glucose cotransporter-2 (SGLT2) inhibitors. SGLT2 inhibitors are an insulin-independent class of oral antihyperglycemic medication that clinicians use in the treatment of type 2 diabetes. Multiple landmark clinical trials support the effectiveness of SGLT2 inhibitors in reducing blood glucose levels, but it is important to understand when to properly utilize them. SGLT2 inhibitors are the most beneficial as an adjunct medication in addition to metformin in patients with a history of cardiovascular or renal disease who need further hemoglobin A1c reduction. The novel mechanism of action also demands clinicians be aware of the side effects not typically experienced with other oral antihyperglycemic drugs, such as genital tract infections, lower leg amputations, electrolyte disturbances and bone fractures. On top of their benefits in type 2 diabetes, novel uses for SGLT2 inhibitors are being uncovered. Diabetic patients with non-alcoholic fatty liver disease, who are at an increased risk of cirrhosis and hepatocellular carcinoma, experience a clinically significant reduction in serum alanine aminotransferase levels. SGLT2 inhibitors are also effective at lowering body weight in obese individuals and decreasing systolic blood pressure. Dual SGLT1/SGLT2 inhibitors are currently being investigated as possibly the first oral medication for type 1 diabetes.Keywords: SGLT2 inhibitors, type 2 diabetes, canagliflozin, empagliflozin, dapagliflozin, ertugliflozin